Perception and Politics: Chinese South Africans in 1980 and 2008 - Suitt, William (Department of Historical Studies, 2023)
In 2008, Chinese South Africans achieved inclusion in the efforts of the government's Black Economic Empowerment policy, following their inclusion was criticism accusing the Chinese of being adjacent to whiteness and therefore undeserving of their victory. This work examines past perceptions of Chinese South Africans to track the shape of the discourse and the later perceptions of Chinese South Africans by their critics in the late 2000s. In engaging with newspapers of 1980 and 1981, non-Chinese can be seen to place Chinese South Africans in an invidious space between apartheid era categorizations of “white” and “non-white.” The conversation on Chinese South African classification intersects in 1980 with an increase in economic ties between the Republic of South Africa and the Republic of China. Association with Japanese through visual similitude in the eyes of non-Chinese, and several special privileges held by the Chinese during apartheid are seen to influence the perceptions held of Chinese South Africans, the boundaries to their perceived status, and the alterations in their status by the 21st century. The Chinese South African community has been featured numerous times over the last half century in articles debating their place in South African society. In the years during and after apartheid, the Chinese South African community was subject to much discussion by nonChinese as to the nature of their identity and that identity's place in a post-apartheid nation. This minor dissertation engages with the language of the discourse on Chinese South African status as it appeared in popular print media in the early 1980s and the late 2000s. Examined in detail was the relationship between perceptions towards Chinese South Africans in 1980 to those in 2008. Language used in 1980 and 2008 tracks the shifting Chinese status in relation to “white” and “non-white” categorizations and displays the role of past perceptions in defining later ones as Chinese space transformed over time. Chinese in South Africa occupied a space neither clearly white or non-white during apartheid and continued to occupy this space in the post-apartheid years. Their amorphous space and visual similarity to other peoples of East Asian descent allowed for Chinese South Africans to be depicted as having been oppressed and having benefitted from apartheid. Chinese South African space, regardless of questions on the nature of their legal classifications over the decades, has been utilized as a tool to depict them in different and opposite ways, all depending on the perspective of the wielder. This minor dissertation displays important elements of the print discourse around Chinese South Africans and their existence between two racial categorizations at points during and after apartheid and details the way that perceived status had been utilized by those featured in print.